A green scarf tied at the foot of the microphone. Musical practices in the interstices between arts, activism and militancy at abortion vigils in 2018 - Millán, Camila (Revista Punto Género, 2023)
In 2018, in different cities of Argentina a series of debates, vigils and mobilizations unfolded around the discussion of the project of Voluntary Interruption of Pregnancy that condensed and enhanced the circulation of feminist narratives in the mass media, institutions, domestic spaces and in the streets. This paper analyzes the musical practices that took place during these massive mobilizations based on the hypothesis that the instances of activism-militancy and the scenes were constituted as spaces that mutually contaminated each other. In the context of the collectivization of political concerns by women and sexual dissidence musicians, enabling the question of the tensions between the artistic, the activist and the militant allows us to situate the public space as the center of political disputes of bodies and territories, taking into account its role in the symbolic shaping of narratives and meanings.